Romeo and Juliet - Shakespeare, William 1564-1616.; Crowther, John (John C.). (New York Spark Pub., 2003)
Presents the original text of Shakespeare's play side by side with a modern version, with marginal notes and explanations and full descriptions of each character.
Keywords: Shakespeare, William -- 1564-1616.; Romeo (Fictitious character) -- Drama; Juliet (Fictitious character) -- Drama; Conflict of generations -- Drama; Vendetta -- Drama; Young adult drama, English; Verona (Italy) -- Drama